Analysis of the Mechanical Resistance of the Lidia Bull Horns. Influence of the Sheathing - Lomillos, Juan Manuel (2022)
The bull horns are the most delicate anatomical part of this animal since its offensive and easily stressful character causes them to suffer traumatic injuries during the year prior to the show. Currently, the horn is protected with a fiberglass sleeve to protect its integrity. The present work studies the mechanical resistance of bull horns, analyzing the possible influence of the sheath on them. For this, horns have been collected from 50 fighting bulls, 4 to 5 years old, 25 of which had been sheathed 6 months before their show. The mechanical resistance of horns has been analyzed in the distal, middle, and proximal parts, using the Instron Electropulse E10000 equipment, following a methodology like that used by Horcajada et al. (2009). Three mechanical resistance tests were performed: direct compression, indirect traction, and flexo-traction; they showed high resistance of the horn, without differences between its different parts. A beneficial effect of the sheath is observed, favoring a greater thickness of the keratin envelope at the proximal part of the horn; the thickness was greater in the sheathed horns. In addition, greater resistance of the horns sheathed is observed in the indirect traction test; the horns of greater longitudinal and diameter resisted the highest pressures, and the corneal bone mostly absorbed the pressure exerted.